Optimization of professional preparation of future teacher of physical culture in informatively-educational space - Dragnev Y. V. (Kharkov National Pedagogical University, 2012)
It is marked that reformation of higher education is an objective necessity. It is marked that the educational system of Ukraine answers the new requirements of informative society not fully. It is certain that optimization of professional education of future teacher of physical culture must be characterized the choice of the most favourable variant of terms and teaching facilities. It is set that transitions within the limits of one informative space have an influence on professional development of future teacher during his studies. The followings terms of optimization of professional education of teacher are selected: system use of active and interactive methods; bringing in to the advanced study; the increase of role is informative of communication technologies in an educational process. The concordance of maintenance of curriculum of education of teachers of physical culture with the programs of education of the European countries and standardization is recommended them within the limits of Ukraine.